Evaluation of Protein Quality of Unfermented and Fermented Blends of Cereal Based Complementary Food Using Rats - Odumodu, C.U. (Pakistan Journal of Nutrition, 2010)
Weanling male rats of 45-55 g were used to compare the protein quality of the unfermented and fermented blends of cereal based complementary food. Paddy rice, parboiled rice, soybean and crayfish were obtained from Jos main market, Nigeria. The paddy rice malted for 72 h and all the foodstuffs were processed into flours. Parboiled rice and soybean mix was formulated in a standard ratio of 70:30 g (PR:DSBO). A modified standard formulation of parboiled rice, soybean, malted rice and crayfish mix in the ratio of 65:25:5:5 g (PR:DSB:MR72:CFo) was made. From the formulation fermentation of different blends at varying periods 24, 48, 72, 96 and 120 h was carried out. Protein content of the unfermented and fermented blends was determined by the standard assay technique. Seven different diets were fed. Five rats were assigned to each diet for 28-days growth studies and a 7-day N balance period. The rats fed the unfermented modified standard (PR:DSB:MR72:CFo) blend had the highest food intake, weight gain, N intake, retained N, BV, and NPU values (69 g, 27 g, 2.96 g, 2.23 g, 83.5 and 75.47, respectively) than the rest of the groups. The result appeared to suggest that fermentation affected the protein quality of the fermented blends negatively making the protein quality of the unfermented modified standard (PR:DSB:MR72:CFo) blend the best.